STUDI POTENSI PANTAI SINDANGKERTA DI KABUPATEN TASIKMALAYA UNTUK PENGEMBANGAN WISATA BAHARI - Suryani, Dietta; Pratikto, Ibnu; Koesoemadji, Koesoemadji (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Sindangkerta Beach in Cipatujah is one of tourism object in South Tasikmalaya which has considerable potential as marine tourism area. The government doesn’t pay much attention makes this area couldn’t develop optimally. In addition, management data is very minimum. The study aims to indentify Sindangkerta Beach potential for marine tourism area. The research was held on February until March 2012. Those months is the last period of the rainy season in Indonesia but it wasn’t discourage the tourists to came to Sindangkerta Beach. The study used description analysis which is describes the real condition in the field and analysis of the suitability of tourism. This type analysis is compared the characteristics and quality of land to land use requirements for specific tourism activities. The result showed that Sindangkerta Beach has many unique things such as upraised coral area, culture attraction and has adequate facilities for supporting tourism activities, Based on the result of Indeks Kesesuaian Wisata (IKW), Sindangkerta Beach is very suitable (S1) for beach recreation. As for Taman Saut the value is 83.57%, for Taman Lengsar is 80% and 82.85% for Ketapang Beach which are the places result into S1 class or very suitable.